Promoting renewable energy consumption in Sub-Saharan Africa: how capital flight crowds-out the favorable effect of foreign aid - Simplice Asongu; Joel Hinaunye Eita (African Governance and Development Institute (AGDI), 2023)
The study assesses the effect of capital flight in the nexus between foreign aid and renewable energy consumption in 20 countries in Sub-Saharan Africa using data for the period 1996-2018. The empirical technique employed is interactive quantile regressions and the following findings are established. Foreign aid increases renewable energy consumption while capital flight dampens the favorable effect of foreign aid on renewable energy consumption. The underlying significance and corresponding mitigating effect are exclusively relevant to the bottom (i.e., 10th) quantile of the conditional distribution of renewable energy consumption. The findings are robust to simultaneity and the unobserved heterogeneity. Policy implications are discussed.
Keywords: H10; Q20; Q30; O11; O55; 330; Foreign aid; capital flight; renewable energy; sub-Saharan Africa